Faktor Penentu Pemilihan Aplikasi Navigasi di Kalangan Pengguna Kendaraan Bermotor Muda - Vivi Triyanti; Marsellinus Bachtiar Wahyu; Frisca Wenlicia; Julian Luke Pranoto (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2025)
With the development and growth of science and technology, various navigation applications are available to everyone, including motorcyclists. The main objective of this study is to provide several aspects that can influence young motorcyclists to choose their navigation application. Samples were taken from 100 motorcyclists aged 18-25 years in the BSD area. The main method used is factor analysis, using SPSS 2021 software as an analysis tool. By implementing KMO and Bartlett's test, the results have passed the validity and reliability tests. Based on the analysis of the size of the sample adequacy (MSA) and Bartlett's test, the anti-image matrix, the component matrix, and the rotated component matrix, there are three factors that can influence motorcyclists aged 18-25 years in the BSD area to choose their navigation application: the quality of navigation services, the features and benefits of the interface, and also the image of the application itself. These factors can be used for future research to analyze their influence on the selection or comparison of several navigation applications with a more specific scope. Furthermore, navigation application developers can consider these three factors to develop their businesses and remain competitive in the market.